Visualization of macrophage subsets in the development of the fetal human inner ear - Steinacher, Claudia; Chacko, Lejo Johnson; Liu, Wei; Rask-Andersen, Helge; Bader, Werner; Dudas, Jozsef; Sergi, Consolato M.; Dhanaseelan, Tamilvendhan; Moreno, Nadjeda; Glueckert, Rudolf; Hoermann, Romed; Schrott-Fischer, Anneliese (Frontiers in Immunology, 2022)
Background Human inner ear contains macrophages whose functional role in early development is yet unclear. Recent studies describe inner ear macrophages act as effector cells of the innate immune system and are often activated following acoustic trauma or exposure to ototoxic drugs. Few or limited literature describing the role of macrophages during inner ear development and organogenesis. Material and Methods We performed a study combining immunohistochemistry and immunofluorescence using antibodies against IBA1, CX3CL1, CD168, CD68, CD45 and CollagenIV. Immune staining and quantification was performed on human embryonic inner ear sections from gestational week 09 to 17. Results The study showed IBA1 and CD45 positive cells in the mesenchymal tissue at GW 09 to GW17. No IBA1 positive macrophages were detected in the sensory epithelium of the cochlea and vestibulum. Fractalkine (CX3CL1) signalling was initiated GW10 and parallel chemotactic attraction and migration of macrophages into the inner ear. Macrophages also migrated into the spiral ganglion, cochlear nerve, and peripheral nerve fibers and tissue-expressing CX3CL1. The mesenchymal tissue at all gestational weeks expressed CD163 and CD68. Conclusion Expressions of markers for resident and non-resident macrophages (IBA1, CD45, CD68, and CD163) were identified in the human fetal inner ear. We speculate that these cells play a role for the development of human inner ear tissue including shaping of the gracile structures.